2019
DOI: 10.1186/s40478-019-0750-2
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of histone acetylation ameliorates disease and metabolic abnormalities in a FUS mouse model

Abstract: Dysregulation of epigenetic mechanisms is emerging as a central event in neurodegenerative disorders, including amyotrophic lateral sclerosis (ALS). In many models of neurodegeneration, global histone acetylation is decreased in the affected neuronal tissues. Histone acetylation is controlled by the antagonistic actions of two protein families –the histone acetyltransferases (HATs) and the histone deacetylases (HDACs). Drugs inhibiting HDAC activity are already used in the clinic as anti-cancer agents. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
93
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 81 publications
6
93
0
Order By: Relevance
“…Statistical analysis was performed by one-way MANOVA followed by Tukey HSD post-hoc analysis: *p ≤ 0.05, **p ≤ 0.01, ***p ≤ 0.001. (Rossaert et al 2019;Tibshirani et al 2015). The finding in the present study that arimoclomol had activity similar to RGFP109 and SAHA in preserving nuclear FUS would argue against a small indirect effect on HDAC activity being responsible.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Statistical analysis was performed by one-way MANOVA followed by Tukey HSD post-hoc analysis: *p ≤ 0.05, **p ≤ 0.01, ***p ≤ 0.001. (Rossaert et al 2019;Tibshirani et al 2015). The finding in the present study that arimoclomol had activity similar to RGFP109 and SAHA in preserving nuclear FUS would argue against a small indirect effect on HDAC activity being responsible.…”
Section: Discussionsupporting
confidence: 41%
“…Acetylation has multiple influences on expression of heat shock and activity of heat shock proteins, dictating the chromatin landscape for binding of HSF1 to HSE (Guertin and Lis 2010) and regulating the activity of HSF1 and HSPs (Marinova et al 2011;Marinova et al 2009;Rao et al 2012;Zelin and Freeman 2015), as well as gene expression and neuronal morphology more generally. Histone deacetylase inhibitors have neuroprotective properties on their own that are relevant to our particular interest, motor neuron disorders (Guo et al 2017;Piepers et al 2009;Rossaert et al 2019;Rouaux et al 2007;Yoo and Ko 2011), including the preservation of mutant FUS, a cause of familial ALS, in the Fig. 4 HDAC inhibitors enhanced expression of Hsp70 induced by the Hsp90 inhibitor, NXD30001.…”
Section: Discussionmentioning
confidence: 99%
“…Because PFKFB3 is known to be a positive regulator of glycolysis, this finding supports a downregulation of glucose metabolism in ALS and is consistent with the results obtained in PET and proteomic studies [23,38,39]. Moreover, we recently showed that HDAC inhibition led to the amelioration of the motor phenotype in a FUS-ALS mouse model [66]. This effect was linked to an increased expression of genes associated with glycolysis, the pentose phosphate pathway, and lipid transport, and to a decreased expression of genes related to fatty acid metabolism, partly restoring mRNA levels [66].…”
Section: Rna Sequencing Of Flux Generating Enzymessupporting
confidence: 89%
“…Moreover, we recently showed that HDAC inhibition led to the amelioration of the motor phenotype in a FUS-ALS mouse model [66]. This effect was linked to an increased expression of genes associated with glycolysis, the pentose phosphate pathway, and lipid transport, and to a decreased expression of genes related to fatty acid metabolism, partly restoring mRNA levels [66]. However, since changes at the transcriptome level do not necessarily translate into changes in the proteome or into functional changes, a fortiori not in energy metabolism, expression studies should be confirmed with functional metabolic studies [73].…”
Section: Rna Sequencing Of Flux Generating Enzymesmentioning
confidence: 99%
See 1 more Smart Citation